Diet and social status in the Lejasbitēni Iron Age population from Latvia. (August 2022) - Pētersone-Gordina, Elīna; Gerhards, Guntis; Vilcāne, Antonija; Millard, Andrew R.; Moore, Joanna; Ķimsis, Jānis; Ranka, Renāte
Highlights: Significant dietary differences were observed between male and female individuals. Evidence for increased social differentiation was consistent with Viking Age. Childhood diet had no relation to differential social status in adults. Abstract: This study reports the first dietary stable isotope data from Iron Age in Latvia. Archaeological, osteological, genetic, and stable isotope data from the Lejasbitēni cemetery were used to study gendered differences in childhood diet expressed in stable isotope ratios with social status expressed in grave goods, in this population from the 7th – 10th centuries CE. Carbon and nitrogen isotope analysis showed significant differences in childhood diet between male and female gendered individuals, indicating that gender might have been a key factor for dietary differences in children. There were no significant dietary differences within the gender groups in adults of differential social status expressed in grave goods, suggesting no link between childhood diet and social status in adulthood, although the sample size was very small. A change towards a more hierarchical society was observed in the later period of the cemetery, expressed in the appearance of more elaborately furnished burials, rare grave goods, and a new burial tradition. All these changes were contemporary with the development of the Viking Age in Northern Europe, and thus possibly signified external cultural influence. Ancient DNA analysis showed that gender as expressed by grave goods corresponded with biological sex in two individuals with the highest quality aDNA, while biological sex could not be confirmed in the other five tested individuals.